Beneficiation of Marine Sands from Les Iles-De-La-Madeleine - Alain Dorval (Canadian Institute of Mining, Metallurgy and Petroleum, 1994)
"''Purification of marine sands from Les Iles-de-la-Madeleine''This paper presents the results of the work that has been done at CRM pilot plant for «Les Silices du Golfe Inc.». Essentially the purpose of this piloting was to demonstrate, on a semi-industrial scale, the process of purification of marine sands from Les Iles-de-la-Madeleine; that had been developed by CRM Process Development Service. This purification is necessary to produce silica suitable for the glass sand and the foundry sand markets.Introduction«Les Silices du Golfe Inc.» is a company who intends to dredge marine sands around the «Les Iles-de-la-Madeleine» coasts. The material will be transported to Gaspesia where electricity, water supply, and a convenient site is available to treat it. A high purity silica intended for glass sand and foundry sand markets will be produced. The objectives of this purification process are to remove organics, calcium, feldspars and iron.Material ReceivedCRM received 50 tons of sand with Si02 varying between 80,6 and 99,3 % (see Figure.1). The highest variations in impurities were the calcium and lost on ignition. We notice direct relation between% SiO2, % CaO and % L.O.I. as you can see on the following Figures 2, 3 and 4."